Propagation and frequency conversion of ultrashort pulses in the presence of coherent nuclear motion - Hartinger, Klaus Karl, author; Bartels, R. A., advisor (Colorado State University. Libraries, 2008)
We have investigated linear as well as nonlinear propagation effects on a relatively weak ultrashort pulse arising from coherent nuclear motion. To this end, we have developed analytical and numerical models used to calculate the molecular response to a strong, ultrashort pump pulse, and propagate a weak probe pulse in the presence of the nuclear wave packet. The molecular response is described in terms of an "effective" susceptibility, which can be split into linear and nonlinear contributions. While a lot of what is discussed in terms of propagation effects is applicable to both rotational and vibrational wave packets, molecular alignment, i.e., coherent rotational motion of linear molecules, is where the focus lies. We have applied spectral interferometry to detect molecular alignment, both in scanning and single-shot configurations, to observe propagation effects due to the effective linear susceptibility, as well as carried out calculations and measurements showing the dependence of the effective third-order susceptibility on coherent nuclear motion. Lastly, a strong enhancement in the conversion efficiency to the third harmonic of a relatively weak probe pulse is observed in a variety of molecular and atomic gases.
Keywords: frequency conversion; molecular alignment; nonlinear optics; quantum dynamics; ultrafast optics; optics